The Dual Nature of Privacy Control: a Review, Framework, and Two Empirical Studies - Cano Bejar, Arturo Heyner (2022)
While some research show that those experiencing enhanced control over their personal information are less concerned about their privacy, other studies are discovering contexts in which enhanced privacy control only worsens people's privacy concern. Thus, this dissertation focuses on two major issues: The nature and antecedent explanations for varying perceptions of privacy control, and the degree in which privacy control goes beyond mitigating concern and affects and behaviors. We specifically argue for the existence of two distinct and parallel types of privacy control-primary and secondary-that recognize the fertile assertion that accepting and adjusting to privacy issues is another healthy response that provides oneself with a feel for control. We use structural equation modelling in the context of social networking platforms (Study 1-a cross-sectional study) and logistic regression in the context of Facebook in mobile devices to deeply understand privacy control. In both studies, the results show that the two types of privacy control correspond separately to increased and decreased information privacy concern and that they arise from culturally derived personal values. Moreover, secondary privacy control strategies seem to be a dominant portion of the current conceptualization of privacy control.